(3SQ GdCSQGQ hYde GdMTGFT hGdCTLGQs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf eSHH GdCSHGH GdPj OYGfj dJCdja cJGH eSCdI TGH JdejP ef Cgd GdCNjGQ jbGd dg eMeO Hf jhfS YGdeG HGdQjGVI hGdYdhe GdWHjYjI GdefWbjI s
(3BNQgG (B:s
(3UaI YTHI GdYGbhd JfHJ aj SGFQ GdHbGY hjbhi aj GdNQja hGdUja JDNP HcQI GdfgGQ hJUa ef GdJQGH LjOG Ke JQV hJcfS aj LhGQ s
(3JHUQI GdeDda (B:s
(3fSHg UGfYG eYLe GdJGQjN GdJQGK Edi (B: 8179- (3eMeO Hf eMeO Hf Ydj GdMdHj GdeYQha HEHf GdTeGY GdeJhaj (B863/1458s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdWHs